2022
DOI: 10.1051/matecconf/202235400007
|View full text |Cite
|
Sign up to set email alerts
|

Stress and psychological resilience in intervention and rescue activities

Abstract: Nature of intervention and rescue personnel activity places them at the top of professions that face a considerable number of occupational health and safety risks. Often, this occupational category does not face a single safety risk, but a complex combination of risk factors, including unpredictability of situations in which they are required to work. Emergence of stress and other psychosocial risks in work processes requires the implementation of an anticipatory attitude and a constant level of vigilance to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Whatever type of work, sooner or later, the period of decreased work capacity occurs and it is reflected in lower productivity, because of fatigue. This state should not be considered the result of a depletion of the functional potential, but primarily as a consequence of nervous control disorders, of various physiological processes caused by work and work environment [8].…”
Section: Exercise and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Whatever type of work, sooner or later, the period of decreased work capacity occurs and it is reflected in lower productivity, because of fatigue. This state should not be considered the result of a depletion of the functional potential, but primarily as a consequence of nervous control disorders, of various physiological processes caused by work and work environment [8].…”
Section: Exercise and Trainingmentioning
confidence: 99%
“…Psychology has shown that interest facets are very varied in relation to social and economic aspects of work management: promotion opportunities, job safety, and opportunity to perform useful work, to perfect profession [8], to surpass oneself, to face risk and be well paid.…”
Section: Psychological Factorsmentioning
confidence: 99%